دراسة مقارنة للفعالية البيولوجية و الكيميائية للنبتتين الصحراويتين الشريك و الحلمة - بن عشور, خميسة; عجيمي, وسام (Université of eloued جامعة الوادي, 2020)
The human need for treatment and the development witnessed by medical science has increased with it the interest in medicinal plants more and more, and from this point of view it became necessary to contribute in this area and that with this research represented in the study of a comparison of the biological and chemical efficacy of the extract of the partner plant fagonia critica.L nipple obtained The extraction process (solid liquid) and (liquid liquid) by the organic solvents represented by hexane, chloroform, ethyl acetate, and n-betanol . The study showed that the partner plant, fagonia critica.L, contains most of the active substances in soap, molluscum, flavonoids, steroids, unsaturated sterols and terpenes, in the absence of alkaloids . The nipple plant, in addition to the partner's wort, contains alkaloids and cardinolides . The antioxidant efficacy was estimated by following the DPPH chemical test, and when comparing the two studied plants, we find that the most effective organic extracts of the partner plant hexane and N-betanol. As for the nipple plant, the most effective organic extract is chloroform, and the partner plant is the best compared to the results of ascorbic acid .
التنوع الحيوي و فسيولوجيا النبات
Keywords: نبتة الشرٌك; نبتة الحلمة; partner's wort; nipple plant; antioxidant potency; organic solvents; extraction